Effects of a school-based intervention program on the smoking behaviors of junior high school students in West Java Province, Indonesia - Rahayuwati, Laili (College of Public Health,University of the Philippines Manila, 2019)
Smoking among adolescents is associatedh additional health and social problems. The impact of smoking is both a threat and challenge to the nation. Schools have particular advantage for educational initiatives because they have access to students and can encourage them to develop knowledge, attitude and practice concerning a healthy lifestyle. This research design was a quasi-experimental study. The research was the intervening program based on reducing or preventing smoking initiation. The data was analyzed inferentially using One Way ANOVA of Dependent Groups/Within Subjects and Independent Group/Between Subjects. Data analysis was assisted by using software STATA and SPSS. Results showed the health education intervention affected positive changes in knowledge, attitude, self-efficacy, and practice either in intervention 1 and 2 groups, even in the Control Group, slight behavior changes were found due to factors of school policy. Meanwhile, the best changes that linearly increased through three time measurements in variables of knowledge, attitude, self-efficacy, and practice were found in the intervention 1 Group. It can be concluded that policy factors determine the success of health promotion and education. On one hand, schools are under the Department of Education and Culture, while community activities are referred to the Department of Homes Affairs. Therefore, improved cooperation these two relevant departments is needed to regulate smoking and enhance the implementation of smoking prevention policies in schools.